Modified Sugarcane Peeler - Kong, Ming Chai; Ang, Zi Xuan; Yahya, Mohd Shahir (Multidisciplinary Applied Research and Innovation, 2022)
This project objective is to design, simulate and fabricate a tool to shorten the time needed to peel the sugarcane manually. The main goal of this project is to successfully create an improvised sugarcane peeler that can act as an alternative to solve the current issue of over-complicated sugarcane peeling process and efficiently shorten the time taken. This is because sugarcane, one of the crude materials to sugar that joins to numerous food products has an expanding in request over the years. However, the sugarcane skin removal takes 65% time of manual harvesting. Deficiency of skilled labour and apparatus for skin removal amid peak harvesting season causes around 10% derivation in selling price. In order to combat this issue, multiple conceptual design and sketches has been created. The idea of having double blades at horizontal and vertical axis for an all side cutting, at the same time fixed by band for a flexible all size sugarcane cutting is produced. Containers were added for more environment friendly operation that does not dirties the surrounding. The SolidWorks 2018 software was used to create the idea and final outcome of the modified sugarcane peeler. By using SolidWorks simulation, the result of drop test for its sustainability and hardness, and also the static test for its stress and strain distribution is collected and analyzed. Based on the result, the product has high ultimate tensile strength, high allowable stress and strain, in other word, the product is suitable for fabrication as it passed both drop test and static test and does not need to be afraid that it might encounter structural failure. The product is ready to be manufactured and will do a great job in increasing the efficiency in sugarcane peeling process.